1975
DOI: 10.1099/00221287-89-1-93
|View full text |Cite
|
Sign up to set email alerts
|

The Location of Bacterial Antigens on Sections of Bacillus cereus by Use of the Soluble Peroxidase---Anti-peroxidase Complex and Unlabelled Antibody

Abstract: SUMMARYThe location of antigens on sections of bacteria using the soluble peroxidaseanti-peroxidase complex in conjunction with unlabelled antibody is described. Using this technique, spore antigens have been detected in the cytoplasm of vegetative cells during forespore septum formation and subsequent stages of sporulation. Antigenic sites were first associated with poly-beta-hydroxybutyric acid granules and subsequently were found in increasing quantities in the cytoplasm of the sporangium. Vegetative cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The appearance of exosporium antigens at the time of forespore engulfment indicates that exosporium synthesis is an 'early' sporulation event. These results agree with those of Short & Walker (1975) and Short et a/. (1977), who used antisera against whole spores and isolated exosporia to localize exosporium antigens immunocytochemically in thin sections of B. cereus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The appearance of exosporium antigens at the time of forespore engulfment indicates that exosporium synthesis is an 'early' sporulation event. These results agree with those of Short & Walker (1975) and Short et a/. (1977), who used antisera against whole spores and isolated exosporia to localize exosporium antigens immunocytochemically in thin sections of B. cereus.…”
Section: Discussionsupporting
confidence: 90%
“…While there are several studies which detail the synthesis of the spore coat proteins (Aronson & Horn, 1969;Nakayama et al, 1978;Uchida et al, 1976), investigation of exosporium synthesis has been restricted to electron microscopy. It has been shown, using immunocytochemical methods, that exosporium antigens are localized within the mother cell compartment during sporulation and are not found in cells before septation (Short & Walker, 1975;Short et al, 1977). Ohye & Murrell(1973) have shown that exosporium development begins during stage IV of sporulation at one pole of the forespore.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, interior antigens would not be detected. Short and Walker (1975) supported this result that staining of B. cereus spores with spore antiserum showed deposits of stain along the exosporium. In our study, the formalin-inactivated spores likely retained other antigenic sites and sectioning was prior to immunolabeling so that antigens throughout the spores could be detected.…”
Section: Fig 1 Location Of Antigenic Determinants In Bacillus Cereusupporting
confidence: 63%
“…Sternberger in 1970 described the technique for the identification of Treponema pallidum in experimentally infected rabbit tissue (10). Little information has since been published on the further development of this test for bacterial identification (8).…”
mentioning
confidence: 99%